All-solution doping technique for high power fiber lasers-refractive index influence in the vicinity of Al: P = 1:1 - Kuhn, Stefan; Hein, Sigrun; Hupel, Christian; Nold, Johannes; Haarlammert, Nicoletta; Schreiber, Thomas; Eberhardt, Ramona; Tu¨nnermann, Andreas (Optics InfoBase Conference Papers, 2017)
A novel and simple solution doping technique is used to explore the refractive index behavior of Al,P-doped SiO2 in the vicinity of the Al:P-ratio of 1:1 at low doping concentrations. It is found that even if Al:P = 1:1 is matched precisely an index increase is observed. This is in contradiction to previous findings in the literature and the already sophisticated models need to be refined in this region.
CRIS-Team Scopus Importer:2023-04-20